Research progress in microstructure evolution of metal materials strengthened by pulsed magnetic field treatment - WANG Huipeng; JIANG Cong; HUANG Yanfei; GUO Weiling; DONG Lihong; XING Zhiguo; WANG Haidou (Cailiao gongcheng)
The pulsed magnetic field treatment technology has the advantages of indirect contact， low energy consumption， green environmental protection， etc.， and has important application prospects in the metal material strengthening. This study summarizes the research status of pulsed magnetic field treatment technology in the strengthening mechanism， numerical simulation， and practical application of metal materials， and puts forward the bottleneck of pulsed magnetic field treatment technology that needs to be broken through. As a kind of high-field strength and periodic magnetic field， the pulsed magnetic field has an obvious strengthening effect on the solid phase transformation and liquid phase transformation of metal materials. The pulsed magnetic field can change the texture and magnetic domain of metal for the solid phase transformation. It can impel dislocations to spread and multiply， speed up the formation of the second phase， and control the order of exudates. During the liquid phase transition， the pulsed magnetic field can provide nucleation energy， break up coarse dendrites， restraint the growth of twisted dendrites， uniform the solute distribution， and eventually enhance the properties of metal. Numerical simulation can reproduce the changes in magnetic field， force， and internal structure in the process of pulsed magnetic field treatment， which provides an important basis for exploring the mechanism of pulsed magnetic field treatment. The strengthening effect of the pulsed magnetic field treatment mainly depends on the magnetic field intensity， pulse duty cycle， and action time of the magnetic field， and one of the key parts of pulsed magnetic field treatment is parameters optimization by numerical simulation. At present， the pulsed magnetic field treatment technology has been applied to cutting tools， coating fabrication， and metal casting. To widen the application of pulsed magnetic field treatment technology， special attention should be paid to strengthening mechanisms， parameter optimization， and device miniaturization in further research of pulsed magnetic field treatment.